THE BLOCK CHARACTER OF THE RECENT TECTONICS OF THE MIDDLE DNIEPER BASIC MAPS DIFFERENCES OF BASE SURFACES - IVANIK, Оlena; SHEVCHUK, Viktor; TUSTANOVSKA, Lyubov; HADIATSKA, Кateryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The tectonic evolution of the Middle Dnipro region in modern times is particularly complex. The presented studies were conducted within the right-bank part of the Middle Dnipro, since the maximum activation of neotectonic activity zones is observed in this region, with significant gradients of the latest tectonic movements and their impact on the formation of the modern relief, that require a comprehensive assessment of the impact of geological and geomorphological factors on their formation.Methods. Structural and morphometric studies within the Middle Dnipro region, using remote sensing methods and spatial-analytical modeling, allowed us to determine morphometric parameters related to the terraced levels of the Dnipro River, the processes of deep erosion, denudation and accumulation, as well as the nature of recent and modern tectonic movements.Results. Detailed interpretation of multi-genetic and multi-order structural and morphometric maps, as well as in-depth geological analysis, allowed us to identify morphostructures and block structures of the crystalline basement (regional blocks and local microblocks), which are distinguished by differentiated tectonic movements and peculiarities of tectonic development.Сonclusions. The neotectonic conditions of formation and development of the paleorelief of the Right Bank of the Middle Dnieper are reconstructed. The peculiarities of the development of terraced levels in the Neogene and Quaternary periods are established. The obtained data can serve as a basis for analyzing the influence of tectonic movements on the activation of hazardous geological processes within the Middle Dnieper region and forecasting their development in the future.
Keywords: paleo-relief; structural and morphometric analysis; tectonic movements; deep erosion; terrace levels; morphostructures; Quaternary period